Clearance of Recombinant Tissue Factor Pathway Inhibitor (TFPI) in Rabbits - Palmier, Mark O; Hall, Lori J; Reisch, Celeste M; Baldwin, Margaret K; Wilson, Alan G E; Wun, Tze-Chein (Thrombosis and Haemostasis, 1992)
The pharmacokinetics of recombinant tissue factor pathway inhibitor (TFPI) after an intravenous bolus injection was studied in rabbits. Clearance of TFPI was followed by measurement of the radioactivity of the 125I-labelled compound in the whole plasma or the trichloroacetic acid precipitate and by quantitation of the functional TFPI activity of the unlabelled compound using a tissue factor-induced coagulation assay. When iodinated TFPI was used, the ratios of the trichloroacetic acid precipitable counts vs. that of the whole plasma was about 1 in the first 10 min after TFPI injection, but this ratio gradually decreased to less than 0.5 after 2 h. This result suggested that the iodinated TFPI in the plasma was partially degraded after prolonged circulation in the animal. When unlabelled TFPI was used, the clearance of TFPI activity from the plasma exhibited bi-exponential elimination kinetics with a rapid alpha phase half-life $$(t1/2α) of 2.3 min, and a terminal beta phase half-life $$(t1/2β) of 79 min. The plasma clearance was 4.2 ml kg–1 min–1. The tissue distribution of intravenously administered 125I-TFPI in the rabbit was studied using whole-body autoradiography. At 3 min after dosing, significant levels of TFPI were apparent in the liver, kidney, and other highly blood perfused tissues. Signficant levels of 125I-TFPI-derived radioactivity were also apparent in the liver and kidney at 30 min after intravenous administration. The localization within the liver demonstrated a mottled appearance, suggesting regions of higher uptake within the liver. In the kidney, the outer cortex consistently revealed the highest activity.